Understanding Customer Intention to Use E-Payment for Online Shopping - Nordin, Noorain Mohd; Talib, Nurul Azlinda Chek; Hasbullah, Nornajihah Nadia; Harun, Hazalinda; Mastor, Suraya Hamimi; Ramly, Fariha Aiza (Information Management and Business Review, 2023)
The emergence of e-commerce has sparked a huge change in consumer behavior, transforming how individuals purchase and conduct transactions. E-payment has become a pillar of this digital transition. However, some customers are still hesitant to adopt e-payment despite its advantages. This paper aims to unravel the factors influencing customer intentions to use e-payment for online shopping. Based on a review of existing literature on the Technology Acceptance Model (TAM Model) and additional external factors, a proposed model was developed to test consumer’s intention to use e-payment for online shopping. The result of this study would be useful to understand consumers’ behaviors in employing electronic transactions when making payments for online purchases. This paper also provides valuable insights for e-payment service providers and online retailers on how to promote sustainable online shopping in the future.